The Implementation of EGRA Technique in Teaching Writing Descriptive Text on 11th Grade Students SMAN 1 Pare - ‘Afifah, Irmafatul (Program Studi Tadris Bahasa Inggris, Fakultas Tarbiyah, IAIN Kediri, 2024)
This study investigates the implementation of the EGRA (Experience, Generalization, Reinforcement, Application) technique in teaching descriptive text to improve students' writing skills. Conducted using a descriptive qualitative design, the research involved observations and interviews with both teachers and students. Data were analyzed and validated through cross-checking and comparison. The findings reveal that the teacher effectively utilized the four stages of the EGRA technique. During the Experience stage, students were asked questions related to descriptive text. In the Generalization stage, students worked in groups. In the Reinforcement stage, groups presented their mind maps. In the Application stage, students completed individual assignments. While all students actively participated in class, some struggled with individual tasks and text analysis. To address these challenges, the teacher employed various strategies such as task-based activities, group work, concept mapping, exercises, authentic resources, and class management techniques, including reducing scores as a form of punishment.